Analisis Implementasi Manajemen Pengendalian Risiko Dalam Upaya Tercapainya Tujuan Organisasi (Studi Kasus Pada Kantor Wilayah Direktorat Jenderal Perbendaharaan Provinsi Nusa Tenggara Barat) - Abdurrahman Abdurrahman; L. Hendra Maniza; Maya Lestari (JIAP (Jurnal Ilmu Administrasi Publik), 2018)
Risk is a threat or command Action or event that emphasizes something to be achieved. In this case it is a very useful management for the various kinds that will arise in the organization. The Regional Office of the Directorate General of Treasury of West Nusa Tenggara Province implements the management of controls in order to enable what will happen in the future which will be arranged properly and appropriately. The purpose of this study is to describe the implementation of risk control management. This research is a qualitative research with descriptive approach. In this research, the researcher describes the implementation and implementation of management by using Edward III analysis that is communication and strategy and steps needed to reach the organization goal. Researchers therefore use, interview, and documentation and then analyze it by digging data, reducing data, displaying data, and reducing conclusions. From these results obtained that there are two indicators of communication in the form of monthly, quarterly and semester, resources with the number and quality and adequate facilities. Then implement the management quickly and effectively with appropriate to reduce the speed and speed of the main goal of the Directorate treasury General of West Nusa Tenggara Province with a scope that is not so large.